Comparative Evaluation Of The Effectiveness Of Perineal And Transrectal Prostate Biopsy In The Diagnosis Of Prostate Cancer - Arsenovich, Abdullaev Radjab; Saniyat Adelevna, Magomedova; Radjabovna, Radjabova Aminat; Hasanovna, Gamidova Patimat; Kurbanovna, Ramazanova Inga; Saipudinovna, Magomedova Patimat; Zaurovna, Abdullaeva Aminat; Murtuzalievna, Murtuzalieva Asiyat; Kurbanovna, Isalabdulaeva Patimat; Kasumbekovna, Gadzhieva Aishat (Journal of Neonatal Surgery, 2025)
In this paper, we conducted a comparative study of the effectiveness of two methods of prostate biopsy — perineal and transrectal — in the diagnosis of prostate cancer. The analysis of the biopsy results of 275 patients with suspected oncopathology allowed us to assess the diagnostic accuracy, the frequency of detection of clinically significant cancer, as well as the complication profile of each method. The data obtained indicate a comparable sensitivity of both approaches, however, perineal biopsy demonstrated a lower risk of infectious complications and better tolerability. The results of the study confirm the expediency of using perineal biopsy in routine clinical practice, especially in patients with a high risk of infections or after unsuccessful transrectal biopsy. The work enriches modern ideas about choosing the optimal method for the diagnosis of prostate cancer and contributes to improving the safety and accuracy of patient examination.